Dynamic Reconstruction of Yttrium Oxide‐Stabilized Cobalt‐Loaded Carbon‐Based Catalysts During Thermal Ammonia Decomposition - Yi Zhu; Hongfei Pan; Qi Li; Xiege Huang; Wei Xi; Haibo Tang; Wenmao Tu; Shihao Wang; Haolin Tang; Haining Zhang (Advanced Science)
Abstract Hydrogen production from the decomposition of ammonia is considered an effective approach for addressing challenges associated with hydrogen storage and transportation. However, their relatively high energy consumption and low efficiency hinder practical multi‐scenario applications. In this study, Y2O3‐stabilized catalysts with Co‐loaded onto porous nitrogen‐doped carbon (Y2O3–Co/NC) are synthesized by pyrolysis of Y(NO3)3‐modified ZIF‐67 under an inert atmosphere, followed by annealing in a reducing environment. The introduction of Y2O3 enhanced the recombination and desorption of N atoms and facilitated the gradual dehydrogenation of NHx on the catalyst surface, resulting in improved catalytic activity for the thermal decomposition of ammonia. Benefitting from the electron‐donating properties of Y2O3 and N‐doped carbon, the optimized catalyst achieved a remarkable NH3 conversion efficiency of 92.3% at a high gas hourly space velocity of 20 000 cm3·gcat−1·h−1 with an encouraging H2 production rate of 20.6 mmol·gcat−1·min−1 at 550 °C. Moreover, the synthesized catalyst undergoes a fast‐dynamic reconstruction process, resulting in exceptionally stable catalytic activity during the thermal decomposition of ammonia, rendering it a promising candidate for carbon‐free energy thermocatalytic conversion technology.